In-Body Sequential Multidrug Delivery Scheme Using Molecular Communication - Tania Islam; Ethungshan Shitiri; Ho-Shin Cho (IEEE Access, 2022)
This study explores the application of molecular communication (MC) for the enhancement of the performance of sequential drug delivery in combination therapy—a multi-drug treatment procedure. To achieve high efficacy, it is essential to maintain a delivery time interval (DTI) between consecutive drug administrations. To this end, this study proposes a coordination scheme that enables the control of the release times of a network of drug-carrying nanomachines to ensure the maintenance of the DTI. Particularly, MC is employed to develop a centralized network, wherein the release times of the drugs from the drug-carrying nanomachines are managed by a controller nanomachine. This nanomachine is named the internal controller nanomachine, as it is placed within the human body. The performance of the proposed scheme is evaluated in terms of the DTI error. Furthermore, the analytical expression of the error is derived and its correctness is validated using simulations.